Morphometric and preliminary genetic characteristics of Branchinecta orientalis populations from Iran (Crustacea: Anostraca) - Atashbar, Behroz; Agh, Naser; Manaffar, Ramin; Stappen, Gilbert Van; Mohamadyari, Ali; Mertens, Johan; Beladjal, Lynda (Zootaxa, 2016)
Branchinecta orientalis is a fairy shrimp endemic to the Palearctic region, from Mongolia to Spain. The patchy nature of its habitat is thought to result in a high degree of subdivision among populations, potentially promoting speciation. We combined morphometric characteristics with molecular phylogeny of cytochrome c oxidase I (COI) to test whether B. orientalis could be a species complex and whether there is any correlation between the genetic variation, morphometric characteristics and geographical variables. We studied six populations from Iran based on the comparison of morphometric and molecular datasets, we confirmed that the Aigher Goli (AIG) population is biometrically well separated from the Akh Gol, Hassar, Rashakan, Khaslou and Garagojanlou populations in northwestern Iran. The relatively high genetic divergence in the AIG from the other populations and its congruence with morphometric data were observed in B. orientalis populations. However, as these results were generated using a small sample size and on a limited sampling range, they should be considered as preliminary.